Analisis Pengaruh Turbine Washing Terhadap Efisiensi dan Daya Pembangkit Turbin Uap - Sagita Firza Nur; I Gede Eka Lesmana (Fakultas Teknik Universitas Pancasila, 2021)
The steam turbine is one of the main components in the Geothermal Power Plant which acts as the prime mover is used to convert heat energy in steam into rotation energy. At PLTP X, steam is used to drive the turbine is in saturation conditions. The principle of the steam turbine is dry steam plant cycle. From July to August, it was known that there have been several decreases in generating power at Unit 2 at PLTP X. The efforts that can be done to overcome this problem is by turbine washing. This study aims to compare the performance of steam turbines based on thermal efficiency, isentropic efficiency and steam turbine generator power before and after turbine washing from the calculation results based on CEI/IEC 953-1, CEI/IEC 60953-3 and ASME PTC 6-2004 standards using the actual steam system operating parameter data collection, interviews and analysis. So that it gets an average increase in isentropic efficiency of 0,0564 %, thermal efficiency of 0,0082 %, the actual power generation of steam turbine is 162,72 kW and the largest power generation reaches 54.500 kW after the turbine washing steam rate of 7,5963 kg/kWh and the turbine heat rate of 3.607,3453 kJ/kWh.